2005
DOI: 10.1097/01.ogx.0000180866.62409.01
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on the Incidence and Treatment of Gynecologic Cancers: A Review

Abstract: After completion of this article, the reader should be able to summarize the clear evidence that obesity is a risk factor for many cancers, including gynecologic malignancies; describe the role of unopposed estrogen in gynecologic cancers; and explain that obese women overall have a poorer survival rate when afflicted with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 100 publications
5
100
0
1
Order By: Relevance
“…29 Obese women may be given lower doses of chemotherapy because the ideal body surface area rather than true body surface area is used to estimate the dose of chemotherapy. [30][31][32] The fact that obese women experienced less toxicity than normal weight women supports that hypothesis, but we did not detect an interaction between obesity and toxicity on breast cancer-specific survival. Other proposed biological mechanisms include higher estrogen levels among obese women that counter the efficacy of tamoxifen and increase cell proliferation, elevated adipokine levels caused by obesity that may accelerate cancer progression, independent effects of insulin, altered immune responses, and oxidative stress.…”
Section: Discussionsupporting
confidence: 59%
“…29 Obese women may be given lower doses of chemotherapy because the ideal body surface area rather than true body surface area is used to estimate the dose of chemotherapy. [30][31][32] The fact that obese women experienced less toxicity than normal weight women supports that hypothesis, but we did not detect an interaction between obesity and toxicity on breast cancer-specific survival. Other proposed biological mechanisms include higher estrogen levels among obese women that counter the efficacy of tamoxifen and increase cell proliferation, elevated adipokine levels caused by obesity that may accelerate cancer progression, independent effects of insulin, altered immune responses, and oxidative stress.…”
Section: Discussionsupporting
confidence: 59%
“…Because of concerns of relative overdosing in obese patients with a large body surface area, it is well documented that empiric dose capping of chemotherapeutic drugs (usually at a body surface area of either 1.8 or 2 m 2 ) occurs in some centers (41). Furthermore some, but not all, observational studies have shown that dose intensity (42) and the cumulative dose (20) of chemotherapy may be lower in obese women (compared with normal weight).…”
Section: Discussionmentioning
confidence: 99%
“…The major modifiable determinants of type 2 diabetes, hyperinsulinaemia and insulin resistance are obesity [4,5] and low physical activity [6], both of which have also been shown to be risk factors for endometrial cancer [6][7][8]. A number of studies have reported a positive association between diabetes and incidence of [9][10][11][12][13][14][15][16][17][18][19][20] or mortality from [21] endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%